2020
DOI: 10.4103/jpgm.jpgm_381_19
|View full text |Cite
|
Sign up to set email alerts
|

Over-the-counter medicines

Abstract: Patients often approach a pharmacist instead of visiting a doctor for minor ailments such as cough, cold, allergies, pain, fever, acidity, diarrhea, and skin-related conditions. Purchase of specific medicines over the counter is legally recognized in most countries. 'Over-the-Counter (OTC) Medicines' means drugs which are legally allowed to be sold by pharmacists without need for a prescription. The term does not have a legal definition in India. Technically, drugs are OTC unless they are specifically stated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 30 publications
0
27
0
1
Order By: Relevance
“…This shows the concern of people living in urban areas seeking health care services. People living in urban areas are more literate, and the urban population is more affluent [19] . However, a significant proportion of people living in rural areas are illiterate and practice superstitions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows the concern of people living in urban areas seeking health care services. People living in urban areas are more literate, and the urban population is more affluent [19] . However, a significant proportion of people living in rural areas are illiterate and practice superstitions.…”
Section: Discussionmentioning
confidence: 99%
“…Policies on dispensing and consumption of over the counter drugs vary globally. In Europen nations, only pharmacies distribute over the counter drugs, but in the United stated, over-the-counter drugs are sold on general retail outlets [19] . In Pakistan, a significant surge in the consumption of over-thecounter drug sales has raised alarming concerns to the local governing bodies [20] .…”
Section: Introductionmentioning
confidence: 99%
“…Since India is one of the largest human antibiotic-consuming countries ( Klein et al, 2018 ), it may have a potentially severe situation in antibiotic resistance. Furthermore, although hospital wastewater reportedly harbors high levels of clinically relevant ARGs ( Fouz et al, 2020 ), the situation might be worse in Indian communities because of a higher prevalence of self-medication that tends to use antibiotics inappropriately ( Marathe et al, 2020 ). Thus far, a few studies using PCR techniques for ARG quantification reported higher load or prevalence of ARGs in hospital wastewater than in municipal wastewater in India ( Lamba et al, 2017 ; Kumar et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The potential risks identified as a result of self-medication practices are delays in going to the doctor, incorrect self-diagnosis, incorrect choice of appropriate medication, therapy, incorrect dosage and administration of the drug, and the danger of interaction with other drugs, diagnosis or occurrence of certain cases of drug addiction or abuse [2]. The incriminating factors that contribute to the practice of self-medication are the inability to access quality medical services, medical fees, lack of time, fear of the doctor or lack of trust in the doctor, as well as insufficient health education [6][7][8]. Recent research shows that another factor that contributes to and maintains the practice of self-medication is the release of over-the-counter (OTC) drugs [8][9][10].…”
Section: Introductionmentioning
confidence: 99%